The coverage on Islam and terrorism: a framing analysis of the international news magazines, Time and the Economist - Yusoff, Sofia Hayati; Hassan, Md. Salleh; Osman, Mohd Nizam; Tamam, Ezhar (Faculty of Modern Languages and Communication, University of Putra, 2014)
Numerous researches have proven that Muslims have been negatively portrayed by the western media for many terrorist attacks or alleged ‘terror plots’ following the 9/11 incident. The media made a deliberate and concerted effort to associate Islam and Muslims with terrorism. As the world mourns the mark of the tenth year of the fateful event, we witness significant events including the electoral presidency of Barrack Obama, the Arabs spring movement and the death of Osama Bin Laden. The events have urged the researchers to uncover the patterns of the framings on Islam and its association with terrorism by the two most influential international news magazines; TIME and The Economist. Using the content analysis approach, the researchers have chosen articles that place a special focus on Muslims or Islam, either directly or indirectly. The rationale for conducting quantitative content analysis is to obtain the labeling tendency and to search for any significant differences in labeling patterns between the four periods selected; one month before Sept 11, one month right after Sept 11, one month after 5 years and finally for one month 10 years after the incident. The sampling procedure for related articles in these two news magazines was based on constructive week basis. Finally, the researchers have made conclusions on the framing patterns; Is Islam still associated with terrorism after 10 years of 9/11 like it was during the most crucial period right after the incident?